Improving of Gelling Capacity of Cooked Crab Meat Proteins - Trejo-Díaz, Gabriela Nallely; Martínez-Maldonado, Miguel Ángel; Uresti-Marín, Rocío M.; Velazquez, Gonzalo; Ramírez, José Alberto (Frontiers in Nutrition, 2021)
Cooked crab meat subjected to a cutting process can aggregate again, forming weak gels. The objective of this work was to determine the effect of two mixing methods, combined with the addition of the microbial enzyme TGase (MTGase) on the mechanical and functional properties of gels from washed or unwashed blue crab (Callinectes sapidus) meat. Live crabs were obtained from Laguna Madre, Tamaulipas, Mexico, and cooked at 120°C for 20 min before hand-picking the meat from the shell. Cooked meat was processed by mixing and cut at temperatures of 25 or 60°C, without (control) or 0.5% of MTGase. Then cooked at 90°C for 15 min. Changes in texture profile analysis, percentage of extractable water, and color were evaluated. The mixing method at 60°C allowed increasing the textural properties of the gels, and the addition of MTGase significantly improved the mechanical properties. The results allowed stablishing a viable technique to obtain restructured gels from cooked crab meat with no need to extract the soluble compounds responsible for their distinctive odor and taste which often affect the mechanical properties.